Organizing the laboratory testing procedures in ischemic stroke patients - Olga V. Lyang; Yulia V. Novozhenova; Irina A. Zhirova (Клиническая практика)
Background: Arranging the laboratory tests for the patients presenting with suspected ischemic stroke, represents an important task for medical organizations. Further treatment tactics may depend on the results of such tests, due to which, it is necessary to assure its high quality at all the stages of laboratory diagnostics. aim: An optimization of the pre-analytical and analytical stages of laboratory testing for the admitted patients, shortening the testing turnaround time (TAT) along with drawing up the organizational decisions together with the clinicists and the quality control department. Methods: The analysis and the rehearsal of the logistical aspects of all the processes related to the hospitalization of acute ischemic stroke patients were arranged by means of organizing the in-house drills and the time tracking of the operations at the admission ward and at the express-laboratory. Results: After performing the in-house timed drills, a number of problems was revealed, both at the admission ward and at the express-laboratory, solving of which has allowed for optimizing the working processes, facilitating the pre-analytical stage and shortening the time of issuing the results. An in-house directive was issued on providing medical aid to the stroke patients, standard operations procedures were drafted and additional adjustments were introduced into the laboratory and medical information systems. The analysis of the regulatory basis has provided a possibility for specificating a number of immunohematological tests for stroke patients and shortening the costs of reagents and expendable materials. Conclusion: For the decreasing the total ТАТ down to 20 minutes for the purpose conforming the quality criteria, it is necessary to shorten the time of pre-analytical and analytical stages. Each medical organization is recommended to arrange the time tracking of all the processes of stroke patient admission for detecting the most time-intensive activities.